High molecular weight glutenin gene diversity in Aegilops tauschii demonstrates unique origin of superior wheat quality - Emily Delorean (Nature Portfolio, 2021)
Delorean et al., along with colleagues from the Open Wild Wheat Consortium, present an analysis of Aegilops tauschii genomes to investigate the origins of the Glu-D1 gene in modern wheats. They discover an abundance of novel Glu-D1 gene alleles that could serve as a reservoir for generating higher quality wheat varieties. This is a companion to the Consortium paper which is available in Nature Biotechnology.